About the treatise of al-Farabi «Kitabul-Khuruf» - Paltore, Y.; Zhumazhanova, F.T. (Journal of Oriental Studies, 2022)
Al-Farabi’s treatise «Kitabul-Khuruf» («Book of Letters») is mentioned. The manuscript of the treatise tells about its publication in the form of a book. Among the treatises of Al-Farabi, a special place is occupied by the book «Kitabul-Khuruf» («Book of Letters»). This is a large and exhaustive treatise in terms of content. The treatise «Kitabul-Khuruf» («Book of Letters») consists of three major sections. Each section covers different topics. For example, metaphysics and its categories, philosophical problems of language and various topics related to language are discussed. According to M. Mahdi, Al-Farabi’s treatise «KitabulKhuruf» («Book of Letters») is recognized as an explanation of Aristotle’s «Metaphysics» and is considered as a comprehensive, interdisciplinary work. As a result of the expansion of the field of study of Al-Farabi’s work, as well as in connection with the translation of the treatise “The Book of Letters”, its theme is not only metaphysics, but also, based on the fact that new topics that have not yet been touched upon appear in other works of Al-Farabi, its processing into the subject area will undoubtedly be carried out. In particular, in this treatise, Al-Farabi, along with metaphysics, comprehensively covers the problem of the origin of language, its development, the connection of language with the sciences, the emergence of scientific terms related to the understanding of philosophy, religion and syllogistic art. The article deals with the issues raised in the treatise of Abu Nasyr al-Farabi «Kitabul-Khuruf» («Book of Letters»). Keywords: al-Farabi, manuscript, Book of Letters, Book of Particles, translation.